3XMM J185246.6+003317 as transient neutron star1. Issue 6 (July 2015) - Hambaryan, V.; Wagner, D.; Schmidt, J.G.; Hohle, M. M.; Neuhäuser, R.
Abstract We performed an X‐ray timing and spectral analysis of the variable source 3XMM J185246.6+003317 to investigate its physical nature. The data from all observations of 3XMMJ185246.6+003317 conducted by XMM‐Newton EPIC MOS1 and MOS2 with the same instrumental setup in 2004–2009 were reprocessed to form a homogenous data set of solar barycenter corrected photon arrival times and high S/N spectra of 3XMM J185246.6+003317. A Bayesian method for the search, detection, and estimation of the parameters of a periodic signal of unknown shape was employed, as developed by Gregory & Loredo (1992, 1993). The results show that 3XMM J185246.6+003317 is a transient neutron star with the genuine spin‐period of 23.11722 (23.11711–23.11727) s and its derivative of 5.3(0.3–5.5)×10–11 s s–1, implying a characteristic age of 7 (6–104) kyr, if the period derivative can be ascribed to the genuine spin‐down rate of the neutron star. The rotational‐phase averaged X‐ray spectra at the different brightness periods can be fitted with a highly absorbed blackbody model with different temperatures. The phase‐folded light curves in different energy bands with high S/N ratio show a double‐peaked profile; the variations depend on time and energy, indicating that radiation emerges from at least two emitting areas. The spectra at the phases corresponding to the maxima in the phase‐folded light curve show different spectral parameters of absorbed blackbody radiation, i.e. the hotter one has a smaller size. The source is detected only from September 2008 to April 2009 with persistently decreasing brightness, but not before, even though it was observed by XMM. Hence, it is a transient neutron star or a binary system hosting it. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)